2006
DOI: 10.1523/jneurosci.5078-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid Accumulation Impairs Multivesicular Body Sorting by Inhibiting the Ubiquitin-Proteasome System

Abstract: Increasing evidence links intraneuronal ␤-amyloid (A␤ 42 ) accumulation with the pathogenesis of Alzheimer's disease (AD). In A␤ precursor protein (APP) mutant transgenic mice and in human AD brain, progressive intraneuronal accumulation of A␤ 42 occurs especially in multivesicular bodies (MVBs). We hypothesized that this impairs the MVB sorting pathway. We used the trafficking of the epidermal growth factor receptor (EGFR) and TrkB receptor to investigate the MVB sorting pathway in cultured neurons. We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
220
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(243 citation statements)
references
References 57 publications
16
220
0
Order By: Relevance
“…In human patients, it is well studied that an increased level of egfr expression is closely related to tumorigenesis (40); however, the relationship between the EGFR pathway and AD is not clear. Previous reports showed that presenilin and Aβ could regulate the expression and metabolism of EGFR, which suggested the involvement of EGFR in the AD process (15,41,42). In our study, enhanced EGFR activity likely resulted from Aβ oligomers-dependent activation, possibly through direct binding.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In human patients, it is well studied that an increased level of egfr expression is closely related to tumorigenesis (40); however, the relationship between the EGFR pathway and AD is not clear. Previous reports showed that presenilin and Aβ could regulate the expression and metabolism of EGFR, which suggested the involvement of EGFR in the AD process (15,41,42). In our study, enhanced EGFR activity likely resulted from Aβ oligomers-dependent activation, possibly through direct binding.…”
Section: Discussionsupporting
confidence: 62%
“…They can be removed through activities of neprilysin, insulin-degradation enzyme, and possibly other mechanisms (5)(6)(7). Aβ is also able to bind with a large array of target proteins, such as EphB2, TNF-R1, RAGE1, and NMDA receptor and prion (8)(9)(10)(11)(12) to exert a wide range of effects, including synaptic transmission, protein transportation, mitochondrial functions, and others (13)(14)(15). Thus, there are a large number of potential targets for developing AD treatment based on the Aβ hypothesis, for example, the mechanisms either reducing the production of Aβ peptides or enhancing the degradation process.…”
mentioning
confidence: 99%
“…Specifically, it reconciles the known extracellular deposition of terminal amyloid plaques in AD patients or AD mouse models (15, 23) with numerous observations from AD patients (33), AD mouse models (34) and Aβ-transgenic Drosophila melanogaster flies (35) showing that Aβ species may also accumulate inside the cell, including MVBs (16,36,37), lysosomes or other vesicular compartments (38)(39)(40). The present observation of an intracellular route of amyloid plaque formation is consistent with observations that extracellular amyloid plaques typically contain a spectrum of proteins that are originally intracellular.…”
Section: Discussionmentioning
confidence: 52%
“…Almeida et al demonstrated that in A␤PP mutant transgenic mice and in human AD brain, progressive intraneuronal accumulation of A␤ occurs, especially in multivesicular bodies (MVBs) [121]. The authors provided evidence that A␤ accumulation in neurons inhibits the activities of the proteasome and deubiquitinating enzymes.…”
Section: Intracellular A␤ Oligomer Toxicitymentioning
confidence: 99%